(untitled) (Journal of Mathematics Mechanics and Computer Science, 2013)
Рассматривается обратная задача продолжения для эллиптического уравнения для модели стационарной диффузии в цилиндрическом слое. Требуется по данным Коши на внешней оболочке неоднородного цилиндра восстановить стационарное поле на внутренней границе цилиндра. Задача сведена к решению трех типов задач Коши для ОДУ второго порядка. На основе необходимых условий минимума функционала невязки выведены формулы в виде рядов для регуляризованного квазирешения задачи. The continuation inverse problem for a solution to an elliptic equation in cylindrical layer for a model of stationary diffusion process is considered. Cauchy data are given on the outer boundary of the cylindrical layer; one need to recover a field at the inner boundary of the cylinder. The problem is reduced to three different Cauchy problems for a second order ordinary differential equation. On the base of necessary minimality conditions of the residual functional analytical formula for a regularized quasisoltion to the inverse problem is derived.